Engaging public servants: public service motivation, work engagement and work-related stress. Issue 7 (15th August 2016) - de simone, Silvia; Cicotto, Gianfranco; Pinna, Roberta; Giustiniano, Luca
Abstract : Purpose: Considering the ongoing international debate on the role of public administrations in economic systems, the interest around Public Service Motivation (PSM) has significantly grown among practitioners and scholars in the past two decades. Following the research streams that have investigated topics of organizational behavior within the public context, this study examines the influence of PSM on public employees' feelings of job satisfaction. The novelty of the study lies in linking some characteristics of the work context presumed to be more prevalent in public organizations with specific job characteristics, regarded as relevant antecedents of job satisfaction. Design/methodology/approach: The study is based on two complementary studies conducted in an Italian public administration. The paper shows how PSM influences job satisfaction, job engagement, and life satisfaction. Findings: This paper shows how PSM influences job satisfaction, job engagement, and life satisfaction. Our findings display how job engagement affects both job and life satisfaction in such contexts. Additionally, the findings display how job engagement affects both job and life satisfaction in such contexts. Research limitations/implications: Although based on a specific context of public administration, the analysis allows some generalizations. Originality/value: Based on these results, the paper contributes to two main streams of the literature. First, it enriches the existing research on PSM by analyzing how it can be managed in complex organizations. Second, it informs the literature on job satisfaction and work-related stress and relates to the intersection between organizational behavior and human resource management that informs the drawing up of HR policies. Furthermore, the paper sheds new light on how to deal with such problems and at the same time opens new avenues for investigations.